Acute pancreatitis as an unusual early postoperative complication after single anastomosis duodeno-ileal with sleeve gastrectomy with duodenal bulb preservation - Palomares, Jaime P. L.; Gómez, Jesús E. O.; Gutiérrez, Manuel A. G.; León, Valeria J.; Barajas, Alberto I. G. (International Surgery Journal, 2025)
Acute pancreatitis (AP) is an infrequent complication after bariatric surgery and is associated with procedures that require close dissection to the pancreaticoduodenal area. Herein this case report presents a case of a 35-year-old male who developed severe acute pancreatitis with necrosis after a Single anastomosis duodeno-ileal with sleeve gastrectomy (SADI-S) procedure with preservation of the duodenal bulb. This complication may result from thermal injury during duodenal dissection near the pancreatic head. Early recognition and careful duodenal dissection using harmonic energy with short bursts and cooling intervals are key to prevent this rare but severe postoperative complication.